2007
DOI: 10.3390/s7091731
|View full text |Cite
|
Sign up to set email alerts
|

Cross-Reactive Sensor Array for Metal Ion Sensing Based on Fluorescent SAMs

Abstract: Fluorescent self assembled monolayers (SAMs) on glass were previously developed in our group as new sensing materials for metal ions. These fluorescent SAMs are comprised by fluorophores and small molecules sequentially deposited on a monolayer on glass. The preorganization provided by the surface avoids the need for complex receptor design, allowing for a combinatorial approach to sensing systems based on small molecules. Now we show the fabrication of an effective microarray for the screening of metal ions a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
24
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 47 publications
0
24
0
Order By: Relevance
“…As long as each component of an array responds to each analyte to a different degree, unique diagnostic patterns for individual analytes will be generated. Up to now, inspired by the superb performance of cross-responsive mammalian olfactory system, considerable efforts have been made to develop sensor arrays for various kinds of analytes such as metal ions (Mayr et al, 2002(Mayr et al, , 2003Lee et al, 2006;Palacios et al, 2007aPalacios et al, , 2008Basabe-Desmonts et al, 2007a), anions (Palacios et al, 2007b;Zyryanov et al, 2007), amino acids (Buryak and Severin, 2005a;Folmer-Andersen et al, 2006), peptides (Buryak and Severin, 2005b), proteins (Zhou et al, 2006), nucleic acids (McCleskey et al, 2003) and carbohydrates (Schiller et al, 2007;Edwards et al, 2007). Compared with conventional methods, molecular imprinting technique (Cormack and Mosbach, 1999;Haupt and Mosbach, 2000;Whitcombe and Vulfson, 2001;Alexander et al, 2006) provides an alternative approach to sensor arrays.…”
Section: Introductionmentioning
confidence: 99%
“…As long as each component of an array responds to each analyte to a different degree, unique diagnostic patterns for individual analytes will be generated. Up to now, inspired by the superb performance of cross-responsive mammalian olfactory system, considerable efforts have been made to develop sensor arrays for various kinds of analytes such as metal ions (Mayr et al, 2002(Mayr et al, , 2003Lee et al, 2006;Palacios et al, 2007aPalacios et al, , 2008Basabe-Desmonts et al, 2007a), anions (Palacios et al, 2007b;Zyryanov et al, 2007), amino acids (Buryak and Severin, 2005a;Folmer-Andersen et al, 2006), peptides (Buryak and Severin, 2005b), proteins (Zhou et al, 2006), nucleic acids (McCleskey et al, 2003) and carbohydrates (Schiller et al, 2007;Edwards et al, 2007). Compared with conventional methods, molecular imprinting technique (Cormack and Mosbach, 1999;Haupt and Mosbach, 2000;Whitcombe and Vulfson, 2001;Alexander et al, 2006) provides an alternative approach to sensor arrays.…”
Section: Introductionmentioning
confidence: 99%
“…13 To this end, a number of fluorescence sensing arrays have been reported that are capable of distinguishing various combinations of metal ions. [14][15][16][17][18][19][20][21][22][23][24] The design of sensors both for selective probes and in arrays typically involves the rational design of each candidate or of a small set of molecules. 25 This is in stark contrast to medicinal chemistry approaches, in which large libraries of molecules are developed, and screened for their suitability.…”
Section: Introductionmentioning
confidence: 99%
“…[5,6] The most commonly used substrates to construct florescent monolayers are noble metals, especially gold and silver, glass, silicon, and metal oxides. [7][8][9][10][11] As metal surfaces emit the plasmon, it can have considerable effect on the photoluminescent properties of the fluorophores, which are present in the monolayers constructed on them. [12] Normally quenching of the fluorescence of the organic fluorophores on metallic surfaces is observed because of the increased nonradiative relaxation of the excited state and because of energy and/or electron transfer from the fluorophore to substrate or vice versa.…”
Section: Introductionmentioning
confidence: 99%